Simulation of Solar Heat Distribution in Buildings Using FormIt Pro Software - Effendi, Andrey Caesar; Wibowo, Danang Harito; Joel, Daniel Bun (MAJ - Malaysia Architectural Journal, 2024)
In a tropical climate like Indonesia, the sun plays an important role in architectural design. Sun simulation allows architects to understand and optimize the impact of sunlight on the building to be designed. It helps in designing sustainable and energy-efficient architectural designs by analyzing access to sun, shade, and natural lighting. Autodesk FormIt Pro is one of the most widely used software in industrial architecture, providing a solar simulation tool that allows architects to evaluate the best performance during the initial design stage. This study aims to provide an overview of the solar distribution simulation with FormIt Pro software in architectural design. The efficient solutions will be found to increase occupant comfort and reduce energy use for cooling. The method used is a simulation using FormIt Pro software, to describe the distribution of solar heat on the skin of the building. This research can help architects and engineers design buildings that are energy efficient. By knowing how to spread the sun's heat over structures, they can design buildings that are more comfortable and use less energy to cool.